The Impact of the Multiple Attempted, Online Homework Assignments on Elementary Students’ Learning: A Case Study in a Private School in Sharjah, UAE - ALHURAINI, OLA ZAIDAN (2023)
The current study has employed a mixed-method research design to investigate the impact of the multiple attempted, online homework assignments (MAOH) on elementary students’ learning outcomes in Math in one private school in Sharjah, UAE. Quantitative data has been collected from grade 2 students through a quasi-experiment, while qualitative data, in the form of semi-structured interviews, have been gathered from both parents and mathematics teachers. Quantitative findings reveal a positive relationship between the MAOH assignments and 2nd grade students’ learning outcomes in Math. However, the impact has been recognized in the knowledge and problem-solving skills only without the reasoning skill. Additional statistical analysis revealed a significant difference in the Math learning outcomes between the experimental class, whose students were allowed to do multiple attempts in their homework, and the control class, whose students were allowed to do a single attempt only. Moreover, qualitative findings indicate the elementary teachers’ and parents’ positive perceptions toward MAOH assignments in terms of learning autonomy and personalized learning, whereas, both negative and positive perceptions in terms of motivation and engagement. In conclusion, the present study has empirically revealed that elementary students’ learning can be increased by implementing multiple attempts at online homework. It highlights the opportunity of having student-centered learning where students’ independency, skills mastery, and personalized learning are all essential components.